The Effectiveness of Music Therapy in Patients with Negative Symptoms of Schizophrenia - Sushmitha Kota; Rakesh Jayantilal Shah (Annals of Indian Psychiatry)
Background: Music therapy is a type of expressive arts therapy that uses music to improve and maintain the physical, psychological, and social well-being of individuals. Studies have shown an impact on depression and anxiety, while there is very little literature that has focused on the negative symptoms of schizophrenia; hence, we aim to study the effectiveness of music therapy in patients with negative symptoms of schizophrenia. Materials and Methods: Seventy-nine patients were randomized to get 40 cases and 39 controls. Cases received music interventions in addition to standard treatment, while controls received only standard treatment. Both cases and controls’ negative symptoms were assessed with the Scale for the Assessment of Negative Symptoms (SANS) before and after music therapy. The Chi-square test, independent t-test, and Mann–Whitney U test were used to determine the associations. Results: We had 36 cases and 31 controls at the end of the music therapy, and there was an association of application of music therapy in negative symptoms of schizophrenia with occupation among cases (P = 0.037). There were huge differences in negative symptoms pre- and postmusic therapy among cases (31.44 ± 9.21) when compared to controls (4.42 ± 5.97) and significant association of affective flattening, alogia, avolition, anhedonia/asociality, and attentional impairment with music therapy (P < 0.00001 each). Conclusions: There is a significant association of each domain of negative symptoms of schizophrenia with music therapy and also improves work efficiency, irrespective of age, gender, marital status, education, and background of the patient with music therapy.